2020
DOI: 10.3389/fpsyg.2020.01530
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Vigorous but Not Moderate Physical Activity Makes People Feel They Have Changed Their Behavior

Abstract: Objective: While behavioral recommendations regarding physical activity commonly focus on reaching demanding goals by proposing "thresholds," little attention has been paid to the question of how much of a behavioral change is needed to make people feel that they have changed. The present research investigated this relation between actual and felt behavior change. Design: Using data from two longitudinal community samples, Study 1 and Study 2 comprised 614 (63% women) and 398 participants (61% women) with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
1
8
0
1
Order By: Relevance
“…This hypothesis is further corroborated by the observed improvements in aerobic fitness, which would likely not be altered without a change in higher intensity-related physical activity. Furthermore, increases in vigorous intensity, but not moderate intensity physical activity, are required for people to feel like they have changed their behaviour (i.e., higher subjective activity) (Szymczak et al 2020). Strategies may be required to prevent compensation via increased sedentary time after engaging in vigorous activity (Rowland 1998;Di Blasio et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is further corroborated by the observed improvements in aerobic fitness, which would likely not be altered without a change in higher intensity-related physical activity. Furthermore, increases in vigorous intensity, but not moderate intensity physical activity, are required for people to feel like they have changed their behaviour (i.e., higher subjective activity) (Szymczak et al 2020). Strategies may be required to prevent compensation via increased sedentary time after engaging in vigorous activity (Rowland 1998;Di Blasio et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While we did this to minimize self-reporting bias and/or recall bias, the data is still self-reported, and our results may be subject to biases. Moreover, a recent report demonstrated that perceptual increase in physical activity is driven by the amount of vigorous physical activity performed, suggesting that an increase in intensive physical activity is important for perceiving a change in one's physical activity ( 81 ). In contrast, smaller changes may need to be sufficient for change to be perceived as such ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected as part of the Konstanz Life Study, a longitudinal cohort study conducted in spring and autumn and spring 2013(Renner, Sproesser, Klusmann, & Schupp, 2012; also see Gamp et al, 2018;Klusmann, Musculus, Sproesser, & Renner, 2016;König, Sproesser, Schupp, & Renner, 2018;Sproesser, Klusmann, Schupp, & Renner, 2015;Szymczak et al, 2020Szymczak et al, , 2021www.uni-konstanz.de/lifestudie). The present study focused on data collected at waves 4 and 5 (spring 2016 and spring 2017).…”
Section: Design and Participantsmentioning
confidence: 99%